Examining the Relationship Between Occupational Balance, Spirituality, and Quality of Life in Older Adults - Yasin Tekeci; Mustafa Cemali; Berkan Torpil (Hacettepe University Faculty of Health Sciences Journal, 2026)
Introduction: This study aimed to examine the relationships between occupational balance, spiritual well-being, and quality of life (QoL) in older adults, and to evaluate the effects of these variables on occupational balance.Methods: This cross-sectional study included 156 volunteers aged 65 years and older without cognitive impairment. Data were collected using the Occupational Balance Questionnaire, the Spiritual Well-Being Scale and the WHOQOL-BREF Quality of Life Scale. Pearson correlation and multiple linear regression analyses were performed.Results: A moderate positive correlation was found between occupational balance and spiritual well-being (r = 0.415; p < 0.001). Occupational balance was also positively correlated with the general health, physical, psychological, social, and environmental domains of QoL, with moderate to strong effect sizes (p < 0.05). Multiple linear regression analysis indicated that the model was statistically significant and explained 39.3% of the variance in occupational balance (Adj. R² = 0.393; p < 0.001). The environmental domain and spiritual well-being were identified as significant predictors (p < 0.05).Discussion and Conclusion: The findings suggest that occupational balance in older adults is associated with spiritual well-being and QoL. Considering environmental factors and spiritual resources may contribute to the development of more holistic approaches in geriatric rehabilitation.